KEISTIMEWAAN MORFOLOGI UNTA PERSPEKTIF AL-QUR’AN DAN SAINS - Syahidah, Ariny; Efendi, Efendi; Faizin, Faizin; syahidah, arinysyahidah (Wahana Islamika, 2025)
Allah, the Almighty Creator who bears the name Al-Qadir (The Omnipotent), holds absolute power over all His creations. Nothing is worthless or in vain in His eyes. In Surah Al-Ghashiyah verse 17, Allah points to the camel as an object worthy of deep observation and reflection: "Do they not look at the camels—how they are created?" The camel is a creature full of uniqueness and remarkable features in its creation, offering numerous benefits to human life. Through a thorough exploration of various sources, it is evident that the purpose behind these wonders is for them to become subjects of contemplation and insight for certain people. Allah refers to this as a reminder for those who possess intellect and reasoning. The Qur’an repeatedly emphasizes that everything Allah has created is a sign, a manifestation of His greatness, and a reminder.